Children living on the street - Kelly, Patricia; Grajcer, Bettina; Rigato, Fatima Dinis (Online Brazilian Journal of Nursing, 2004)
Children who spend part or all of their developmental years living on the streets constitute a vulnerable population. Local and national governments are in great need of research-based programs to supplement their efforts at providing health and social services. This article provides a review of what is known about children living on the street, describes a Sao Paulo program that works with this population, and makes suggestions for research that nurses might undertake.